Assessing the severity of the novel influenza A/H1N1 pandemic. (14th July 2009) - Garske, Tini; Legrand, Judith; Donnelly, Christl A; Ward, Helen; Cauchemez, Simon; Fraser, Christophe; Ferguson, Neil M; Ghani, Azra C
Abstract : A major concern about the emergence of the novel strain of influenza A/H1N1 is the severity of illness it causes. Tini Garske and colleagues propose methods to obtain accurate estimates of the case fatality ratio as the pandemic unfolds